Collected works of H.S. Tsien (1938-1956) - Qian, Xuesen, 1911-2009 (Academic Press, 2012)
Dr. H.S. Tsien (also known as Dr. Qian Xuesen), is celebrated as the leader of the research that produced China's first ballistic missiles, its first satellite, and the Silkworm anti-ship missile. This volume collects the scientific works of Dr. H.S. Tsien (also known as Dr. Qian Xuesen) and his co-authors, which published between 1938-1956 when he was studying and working in the United States as a graduate student, scientist and professor, when aeronautic exploration stepped up from low speed to high speed regimes and astronautic technology entered its infant stage. The author is one of the most significant Chinese scientists in the past 70 years. Focuses on a series of key problems in aerodynamics, stability of shells, rocket ballistics and engine analyses. Collects Tsien's work as author and co-author from his time working in the US.